Integration Protocol Student Academic Information to Campus RFID Gate Pass System - Hendra Gunawan; Evizal Abdul Kadir (IAES Indonesia Section, 2017)
Nowadays, security is a part that consent by many institution including academic for example in University campus, some of campus have been implement automatic system in campus area to control visitor to enter University also for the staffs and students, but the system is in standalone with introduce new gate pass. Most of University has been use Information Technology (IT) in application for academic system such as student information, registration, results information, etc. In this paper discuss on integration of student information to gate pass system then do not require new card or pass for every student to enter campus area. Gate pass system is required information to match to database that who allow entering to campus, normally a new database is create for the system. In this case, University has student and staff database including lecturer, thus to be efficient the data in existing database can be use and integration using protocol that gate pass system give a command to database as request then verification of those data. Currently, student database stored in server room and the place far away from gate pass system, in order to make it transaction faster for visitor to enter then a mini database is setup onsite of gate system, but periodic updating is require or every new update in database. Results shows, database stored in student information system is more than 30,000 number of student and transaction time is less than 1 second and in average cycle time is 5.5 seconds for motorcycle lane and 7 seconds for car, that mean time for visitor to access gate pass system for entry campus is most reasonable.